The Role of Social Support in Improving Treatment Compliance in Tuberculosis Patients: A Meta-Analysis - Hendra Dwi Kurniawan; Rizki Aqsyari; Fara Khansa Azizah (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Tuberculosis is a disease that requires attention in global health issues. Tuberculosis is a disease with a high mortality rate. Although a cure for tuberculosis has been discovered, the treatment process remains challenging, particularly the length of treatment. Tuberculosis patients often fail to complete their treatment due to the lengthy duration. Support from loved ones and a supportive environment is crucial for tuberculosis patients during their treatment. With this support, tuberculosis patients will have a support system that can assist them in their treatment. This study aims to estimate the effect of social support on treatment compliance in tuberculosis patients. Subjects and Method: This study used a systematic review and meta-analysis using PICO. Population: tuberculosis patients. Intervention: social support. Comparison: no social support. Outcome: treatment adherence. The articles used in this study came from 2 databases, namely Google Scholar and Science Direct. The keywords of the article are